Discourse and the logic of education reform: crisis narratives in Kansas - Kerr, Jessica Preston (Kansas State University, 2016)
Discourse analysis (DA) explores the relationships between discursive practices and wider social and cultural structures, relations, and processes. In this paper I explore, through a qualitative DA of education reporting in the Topeka Capital Journal (January 2014- January 2016), state press releases, and gubernatorial state speeches, how notions of fiscal crisis, both material and narratively cultivated, function to underscore the logic of neoliberalism. While considering potential context specific properties of local reporting and the cultural, geographical, and historical context of the region, I connect my findings with the larger, scholarly body of work pertaining to these issues. Connecting media language and policy discourse across local and global dimensions adds to a growing theoretical and qualitative understanding of the facets of education restructuring and reform within the framework of the global movement and adds material resources in the form of analysis as tools for educational practitioners and grassroots organizations working to craft alternatives to the neoliberal doctrine.
Keywords: Education; Discourse; Critical Media Literacy; Kansas